Socio-psychological diagnostics and forecasting protest behavior of youth in the digital environment - R. V. Len’kov; O. A. Kolosova; S. V. Kovalyova (Цифровая социология)
The article provides the results of a search empirical study of the impact of digital communications on the protest behavior of young people in the digital environment. The authors conducted the study on the basis of the State University of Management from November 2019 to April 2020. In the course of its implementation, the civil and political practices of student youth during the first wave of the COVID-19 pandemic and mass self-isolation were studied and updated. The paper determines the most common forms of protest activity of university students, names the main reasons for their participation or non-participation in mass protest actions. It has been empirically proven that the increase in protest behavior of young people is determined by an increase in the amount of political information with a high number of likes and reposts. In order to deactivate protest moods among young people, reduce the threats of their protest behavior and improve attitudes towards the authorities, the authors developed practical recommendations that involve social monitoring of sites, forums, pages and communities on the Internet, where young people can freely express their opinions, express dissatisfaction, and receive explanations about the actions of the authorities. The study also recommends to stimulate “feedback” with the authorities, improve public opinion on the actions or inaction of the authorities, increase the influence of citizens’ assessments on the work of state and municipal authorities. The paper states the importance of tracking youth groups prone to extremism, carrying out preventive measures with students in schools, students in colleges and universities, teaching them legal literacy. To get answers to questions about the political and economic consequences awaiting our country after the end of the coronavirus pandemic, as well as about the essence of the predicted threats, the authors plan the study on a more representative sample.